(untitled) (Altre Modernità, 2022)
In search for a constructive response to the Covid pandemic, which exacerbated rather than caused the current crisis of university education, this article reports an implementation process of student-oriented teaching practices into an ESP curriculum of management-oriented study at a technological university, i.e., in an interdisciplinary environment, which, perhaps paradoxically, struggles with interdisciplinary approaches, deindividuation, compartmentalization of learning, and, consequently, with varying degrees of student engagement. Exploring students’ (in-)ability and (un-)willingness to become autonomous learners in the Covid era and beyond, the authors rethink students’ exposure to pedagogical tools and methods designed to foster student autonomy and combat instructional monotony including networking, telecollaboration, language coaching, alternative assessment methods, and discuss consumption of online education in general. Face to face with the volatile dynamics of technologically mediated interactions and evolving teacher/student roles, the article critically assesses the growing emphasis on students’ autonomy which is – much like the ability to cope without social contact – often taken for granted rather than systematically trained.